THE IMPACT OF JOB STRESS, ROLE AMBIGUITY, WORK-LIFE IMBALANCE, WORK ENVIRONMENT, AND PERCEIVED ORGANIZATIONAL SUPPORT ON ORGANIZATIONAL COMMITMENT (Case Study Of Nurses At Private Hospital X In Central Jakarta During 2023) - Karina Natalie Kuntjoro; Yohana F. Cahya Palupi Meilani (SEAN Institute, 2023)
Healthcare delivery depends heavily on nurses. Nursing staff organizational commitment levels are closely related to the efficiency and standard of care that healthcare facilities deliver. One of the elements that affects an employee's retention is their level of organizational commitment. Private hospital X in Central Jakarta had a problem retaining its health workers, which shows a lack of employee commitment to the organization. The purpose of this study was to determine the effect of job stress, role ambiguity, work life imbalance, work environment, and perceived organizational support on organizational commitment. In this study, the cross-sectional method is used to get quantitative data from an online questionnaire. The questionnaire was modified based on pre-existing questions from earlier literature. Data were gathered purposefully from a group of 160 permanent nurses who had worked at private hospital X for at least one year using a non-probability sampling technique. PLS-SEM software was then used to analyze it. The results showed that job stress, role ambiguity, work-life imbalance, work environment, and perceived organizational support affect organizational commitment among nurses in Private Hospital X in Central Jakarta. The study is anticipated to offer guidance for the hospital to improve the organizational commitment of its nurses.